Monocytes as Regulators of Inflammation and HIV-Related Comorbidities during cART - Joshua J. Anzinger; Tiffany R. Butterfield; Thomas A. Angelovich; Suzanne M. Crowe; Clovis S. Palmer (Journal of Immunology Research)
Combined antiretroviral therapy (cART) extends the lifespan and the quality of life for HIV-infected persons but does not completely eliminate chronic immune activation and inflammation. The low level of chronic immune activation persisting during cART-treated HIV infection is associated with the development of diseases which usually occur in the elderly. Although T-cell activation has been extensively examined in the context of cART-treated HIV infection, monocyte activation is only beginning to be recognized as an important source of inflammation in this context. Here we examine markers and sources of monocyte activation during cART-treated HIV infection and discuss the role of monocytes during cardiovascular disease, HIV-associated neurocognitive disorder, and innate immune aging.